Which firms employ older workers? - Daniela Andrén; Lackson Daniel Mudenda; Nicklas Pettersson (Örebro University School of Business, 2019)
There is an increasing emphasizes on the importance of allowing people as they grow older to continue to work according to their work capacity and preferences. This paper builds on earlier literature that shows that firms employ older workers, but they tend not to hire them, and provides an explorative analysis of the establishments that employ older workers. A special focus is on how sensitive are the findings when the definition of older workers become more restrictive. Using employer-employee data from Swedish administrative registers, we found that the difference in establishments' employment is large enough to explain some of the observed difference across definitions. The retirement age in the guaranteed pension scheme, i.e., 65 years, seems to be one the institutional settings that affect both the employees and employers' decision for work after 65, but also the establishment's size, age and ownership.
Keywords: J21; J22; J23; J24; J26; 330; active aging; older workers; establishments; firms